Sokongan psikologi dalam perniagaan kepada usahawan belia kurang upaya fizikal - Mohhairil Isaruddin,; Aizan Sofia Amin,; Nur Saadah Mohamad Aun, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Generating income is difficult in the current situation, especially for people with disabilities. This study explores the form of business support obtained by young entrepreneurs with physical disabilities, engaging with entrepreneurial activities. This study's design uses an entirely qualitative approach, i.e. case study, using in-depth interview data collection method. Interviews with study participants were conducted in a semi-structured manner and used purposeful sampling. The data obtained were analyzed thematically. The sampling of the study involved eight youth entrepreneurs with physical disabilities in Selangor. The study results found two types of support, namely the tangible and intangible. Tangible supports are finance, skills/knowledge, and materials/equipment. Intangible supports are family/spouse, friends and counsellors / JKM / SOCSO Rehabilitation Center. The implications of this study are to provide appropriate input in designing suitable programs to improve the form of business support to physically disabled youth entrepreneurs in Malaysia.